Leaving behind their legacies - Abd Razak, Dzulkifli (2005)
TWO very wellloved personalities passed away last week, one abroad and the other at home. Internationally, the world mourned the death of one of the past century’s literary greats, Ba Jin, at the age of 101. Also known as Pa Chin, he is one of the most widely read Chinese writers of the 20th century. Arguably his novel, Family, has become required reading in many university courses throughout the world on the history of China and East Asia. It is one of three novels regarded as bestsellers. The other two are The Spring and The Autumn. The novels generally draw on the struggles and tragedies, hate and love of the young generation in a saga of familial decline.